PENGGUNAAN MEDIA PEMBELAJARAN BENDA DI SEKITAR ANAK TERHADAP KEMAMPUAN MEMBANDINGKAN DALAM PEMBELAJARAN MATEMATIKA BAGI SISWA TUNARUNGU KELAS II SLB - Oktaviani Putri, Triwidiya (Jurnal Pendidikan Khusus, 2016)
Abstract Hearing impairment would have disturbance if the information which the children obtained was in the form of verbalization, because it required listening ability and thinking training. Therefore hearing impairment children had obstacle in understanding the abstract things, such as mathematics. Hence it needed to develop ability to learning mathematics, one of them was comparing using things around children as learning media because they were easy to find and fast to be recognized so that they could attract the children desire. This research had purpose to describe whether there was influence of using things around children learning media toward comparing ability in learning mathematics to class II hearing impairment students in SLB Asih Mulya. This research used quantitative approach with pre Experimental kind and one group pretest and posttest design. The independent variable was “things around children learning media” and the dependent variable was “comparing ability”. The subject was class II hearing impairment students numbering 6 people. The data collection used writing test and the data analysis used sign test. This research result indicated that There was enhancement of average value of comparing ability i.e. pre-test was 33.33 and in post-test the value became 70. Zh value obtained was 2,05 and Z table 5% to two sides test was 1,96 so it could be concluded that Ho was refused and Ha was accepted. Based on the explanation above it could be concluded that there was significant influence of using things around children learning media toward comparing ability in learning mathematics to class II hearing impairment students in SLB Asih Mulya Pamekasan.   Keywords: Learning Media, Things Around children